2021
DOI: 10.1186/s12889-021-10710-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resilience on anxiety and depression among grass-roots civil servants in China

Abstract: Background The grass-roots civil servants are the final implementers and executors of a series of government policies and the fundamental force for social stability and harmonious development. However, the mental health problems of grass-roots civil servants have not got full attention. This study aimed to assess the impact of resilience on anxiety and depression among grass-roots civil servants in China. Method From Oct to Dec 2019, 302 civil serv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…26 Another study of public servants had confirmed resilience as an effective mediator and moderator when explaining the association between stress, anxiety, and depression. 27 Similarly, we have investigated the role of resilience, which would intervene the relationship between depression and anxiety reactions during the pandemic. 28 We verified a hypothesis that resilience could provide appropriate coping strategies for public servants to overcome mental stress during the pandemic.…”
Section: Public Workers' Distress Public Service Motivation and Work ...mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another study of public servants had confirmed resilience as an effective mediator and moderator when explaining the association between stress, anxiety, and depression. 27 Similarly, we have investigated the role of resilience, which would intervene the relationship between depression and anxiety reactions during the pandemic. 28 We verified a hypothesis that resilience could provide appropriate coping strategies for public servants to overcome mental stress during the pandemic.…”
Section: Public Workers' Distress Public Service Motivation and Work ...mentioning
confidence: 99%
“…48 Additionally, it has been noted that public servants' anxiety is highly correlated with depression and resilience mediated the association between stress, anxiety, and depression during the nonpandemic years. 27 Consequently, anxiety reaction, regardless of whether it was derived from the viral pandemic or not, contributes to depression and resilience acts as a mediator between them in case of public workers.…”
Section: Viral Anxiety Depression and Resilience Of Public Workers Du...mentioning
confidence: 99%
“…In general, three models of resilience are being tested in past research; compensation, protection and challenge models. The compensatory model tests the direct effects of resilience, whereas the protection model tests the indirect (mediated) effect ( Song et al, 2021 ). Individuals experiencing a high level of COVID-19-associated fears, apprehensions, worries and anxieties are confronted with a high level of COVID-19 burnout due to adverse life challenges during a pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In China, most studies on resilience focus on the investigation of negative emotions such as anxiety and depression (Hou et al, 2021 ; Lau, 2022 ; Song et al, 2021 ; Zhang et al, 2020 ). The research on the resilience of patients with diabetes mainly focuses on the related research on mental resilience and quality of life (Luo, Guo, et al, 2021 ; Mei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%